Answer:
g(x) will eventually exceed f(x) because g(x) is an exponential function.
Explanation:
From the first table we can observe the following patterns:
![f( - 1) = {( - 1)}^(2) - 6 = - 5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ugh7by1zux04icdmxzex0bassioqv74f9p.png)
![f(0) = {( 0)}^(2) - 6 = - 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/v9wo062ctsr7uvh7swmf8idwsu2he4h41q.png)
![f( 1) = {( -1)}^(2) - 6 = - 5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/x24bww8ufx54hjb9t0ftcl2sobvhl8eb2f.png)
![f(2) = {( 2)}^(2) - 6 = - 2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7moxmcaiz5ejrwshsjdmmorl8t6xno2a15.png)
In general,
![f(x) = {x}^(2) - 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vivz48i3fvzuxrve7mc08laod0bm01om2f.png)
From the second table we can observe the following pattern:
![g( - 1) = {6}^( - 1) = (1)/(6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7yev2gcfr6xnyvn1irr5dy6gz1dv9sw7e6.png)
![g(0) = {6}^( 0) = 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/no44ma11yp6avtu44cxwzzash6b7bxrv9d.png)
![g(1) = {6}^(1) = 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k5bskljebu1wqnsyo22gvx23h2al67f4l1.png)
![g(2) = {6}^(2) = 36](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7dc9l93ieoyh03la4rclxtzlyqulbfkklt.png)
In general,
![g( x) = {6}^( x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8celt3hew7wa1tlydwdisrmnq91g3wiz5c.png)
Conclusion:
Since the f(x) represents a quadratic function and g(x) represents an exponential function, g(x) will eventually overtake f(x).
The correct answer is C.